Preclinical and preliminary clinical reports for successful treatment of ovarian cancer with standard treatments in combination with epigenetic modifiers in a complimentary and integrative approach. Issue 2 (5th March 2019) - Nezami, Mohammad; Garner, Jessica
No abstract available